REPRESENTAÇÃO NEGRA NA LITERATURA BRASILEIRA: DOS ESTEREÓTIPOS AO AFROFUTURISMO - Wirz, Gabriel (Inventário, 2025)
This paper reviews the bibliography on problematic representations of black people in Brazilian nineteenth-century literature up to contemporary productions written under the category of afrofuturism. Here we also criticizes the constitution of a national literature and canon elaborated by a segregational and artificial process of national construction, which chose pretentious portraits of indian people as national heroes, a social process that outcasted black people and characteristics associated to afro-diasporic culture. To think of Afrofuturism, a text by the writer Kodwo Eshun was chosen as a theoretical guideline. Besides it, we chose texts by Souza and Quiangala. Thus, in this paper the afrofuturist movement is conceived as a multimedia and intellectual afro-diasporic manifestation, which can mitigate colonialist, epistemicides and racist discourses.